Pragmatic and Discourse Functions in Jenifa’s Diary - Bamgbose, Ganiu; Ehondor , Beryl (Linguistik Online, 2021)
Existing studies on comedies in Nigeria have focused mainly on stand-up comedy, with little attention devoted to situation comedies. This study, therefore, investigates the pragmatic acts that are used to reflect inherent societal issues revealed under the guise of humour in a Nigerian sitcom, Jenifa’s Diary. Drawing excerpts purposively sampled from the first three seasons of the sitcom and subjecting them to the analytical tools of Jacob Mey’s pragmatic acts and Meyer’s functions of humour, the study shows the discourse functions of social and moral consciousness which address issues of incivility, domestic violence, poor etiquette, lying and indecent dressing. These discourse functions are achieved through the practs of warning, informing, enculturating and advising, and the communication functions named enforcement and differentiation. The study concludes that sitcoms are not just scripted to amuse viewers but also to address the state of the nations where they are set.